Comparison of revascularization and conservative treatment for hemorrhagic moyamoya disease in East Asian Countries: a single-center case series and a systematic review with meta-analysis - Zhang, Xiang-Hua; He, Jun-Hua; Zhang, Xiang-Sheng; Zhang, Jing; Wang, Cheng-jun; Dong, Yi-Peng; Tao, Wu (Frontiers in Neurology, 2023)
Objective: The better treatment option between the revascularization and conservative treatment in hemorrhagic moyamoya disease (HMMD) is still under controversy, our single-center case series and a systematic review with meta-analysis aim to analyze and identify whether the surgical revascularization will lead to a significant reduction of the postoperative rebleeding, ischemic event, and mortality, compared with conservative treatment, in the East Asia HMMD patients. Methods: A systemic review of literatures searched from PubMed, Google Scholar, Wanfang Med Online (WMO), and China National Knowledge Infrastructure (CNKI) was performed. The outcomes of surgical revascularization and conservative management, including the rebleeding, ischemic event, and mortality, were compared. The authors institutional series of 24 patients was also included and reviewed in the analysis. Results: Both 19 East Asia studies including 1571 patients and our institution retrospective study of 24 patients were included. In the adult patients only studies, the rebleeding, ischemic event, and mortality were all significantly lower in revascularization patients than in conservative ones (13.1% (46/352) versus 32.4% (82/253), P<0.00001; 4.0% (5/124) versus 14.9% (18/121), P=0.007; and 3.3% (5/153) versus 12.6% (12/95), P=0.01, respectively), and in the adult /pediatric patients’ studies, similar statistical results of the rebleeding, ischemic event, and mortality have been obtained (11.9% (70/588) versus 25.6% (103/402), P=0.003 or <0.0001 in a random or fixed-model respectively; 14/296 (4.7%) versus 26/183 (14.2%), P=0.001; and 4.6% (15/328) versus 18.7% (23/123), P=0.0001, respectively). Conclusion: The current single-center case series and systematic review with meta-analysis of studies suggests that the surgical revascularization, including direct, indirect, and combination of both, significantly reduces the rebleeding, ischemic event, and mortality in HMMD patients in East Asia region. More well-designed studies are warranted to furtherly confirm these findings.